2006
DOI: 10.1152/ajpheart.00290.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Type II diabetes on capillary hemodynamics in skeletal muscle

Abstract: Microcirculatory red blood cell (RBC) hemodynamics are impaired within skeletal muscle of Type I diabetic rats (Kindig CA, Sexton WL, Fedde MR, and Poole DC. Respir Physiol 111: 163-175, 1998). Whether muscle microcirculatory dysfunction occurs in Type II diabetes, the more prevalent form of the disease, is unknown. We hypothesized that Type II diabetes would reduce the proportion of capillaries supporting continuous RBC flow and RBC hemodynamics within the spinotrapezius muscle of the Goto-Kakizaki Type II di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 52 publications
3
92
1
Order By: Relevance
“…Elegant modeling studies by Groebe and Thews (Groebe & Thews, 1986) and Friederspiel and Popel (Federspiel & Popel, 1986) have suggested that the total number of red blood cells that lie adjacent to a muscle fiber is the primary determinant of the diffusion capacity of O 2 (DO 2 ). In turn, the DO 2 is a Kindig et al, 2002;Richardson et al, 2003;Russell et al, 2003;Behnke et al, 2005;Padilla et al, 2006). In the rat, one of the muscles commonly used to examine the microcirculation is the spinotrapezius muscle Kindig et al, 2002;Russell et al, 2003).…”
Section: Aging-induced Alterations Within the Microvasculaturementioning
confidence: 99%
See 1 more Smart Citation
“…Elegant modeling studies by Groebe and Thews (Groebe & Thews, 1986) and Friederspiel and Popel (Federspiel & Popel, 1986) have suggested that the total number of red blood cells that lie adjacent to a muscle fiber is the primary determinant of the diffusion capacity of O 2 (DO 2 ). In turn, the DO 2 is a Kindig et al, 2002;Richardson et al, 2003;Russell et al, 2003;Behnke et al, 2005;Padilla et al, 2006). In the rat, one of the muscles commonly used to examine the microcirculation is the spinotrapezius muscle Kindig et al, 2002;Russell et al, 2003).…”
Section: Aging-induced Alterations Within the Microvasculaturementioning
confidence: 99%
“…Recently, our laboratory has utilized a modified form of the rat spinotrapezius muscle preparation for observation of microvascular function via video microscopy in health disease Padilla et al, 2006) and aging (Russell et al, 2003) research. The spinotrapezius represents an excellent muscle for microscopic analysis due to its mixed fiber type composition (Delp & Duan, 1996) and oxidative capacity similar to that of the human quadriceps (Leek et al, 2001).…”
Section: Chapter 1 -Introductionmentioning
confidence: 99%
“…These effects impact the fine balance of O 2 delivery-to-O 2 utilization, at least within the spinotrapezius muscle, such that very low Pmv O 2 values are evident at rest and both during and following contractions (6,37,38). It is conceivable that the ϳ60% fast-twitch fibers that comprise the spinotrapezius (13) are driving these aberrant Pmv O 2 profiles.…”
mentioning
confidence: 99%
“…Thus, Type 1 diabetes induces muscle atrophy, capillary rarefaction, and impaired vascular and capillary hemodynamics as well as reduced muscle oxidative capacity (3,16,38). Type 2 diabetes also presents a severe impairment of arterial (19,34) and microcirculatory (27,28) hemodynamics in skeletal muscle at rest and during exercise. Key contributors to this condition are thought to include upregulation of endothelin-1 (37), prostaglandin (1), and myogenic (43) vasoconstrictor pathways combined with downregulation of vasodilatory endothelial function and nitric oxide bioavailability (17,24,48).…”
mentioning
confidence: 99%
“…Thus, at present, there is no clear mechanistic answer to why the time course of HBOinduced vasoconstriction, as inferred from the Pmv herein, may be impaired in DIA. On the other hand, the vascular adaptation dynamics in response to increased muscle energetic demands in DIA are slowed (2), and microcirculatory function is compromised (16,27 (Fig. 4, reviewed in Ref.…”
mentioning
confidence: 99%